THE ROLE OF PLANT GROWTH REGULATORS IN THE INDUCTION OF CALLUS TREATED WITH HARMEL SEEDS EXTRACT AND THE REGENERATION AND ROOTING OF VEGETATIVE GROWTHS OF BARLEY VARIETIES IN VITRO: THE ROLE OF PLANT GROWTH REGULATORS IN THE INDUCTION OF CALLUS TREATED WITH HARMEL SEEDS EXTRACT AND THE REGENERATION AND ROOTING OF VEGETATIVE GROWTHS OF BARLEY VARIETIES IN VITRO (Iraqi Journal of Market Research and Consumer Protection, 2026)
An experiment was conducted in the Plant Tissue Culture Laboratory at the College of Agricultural Engineering Sciences, University of Baghdad during the years 2022-2023 using Plant Tissue Culture Technique. The variables three varieties of barley: Ebaa265, Ebaa99 and Bouhoth 244; 2,4-D (2,4-Dichlorophenoxyacetic acid) at concentrations: (0,1.5,3 and 4.5) mg.L-1  for callus inducation; BA (Benzyl Adenine)  at concentrations: (0,1,2, and 3) mg.L-1  for regeneration and  IBA (Indole Butyric Acid) at concentrations :(0,1,2, and 3) mg.L -1 for rooting ,using MS (Murashige and Skoog) media. Measurements has taken on average of the weight wet and dry of the callus and number and length shoot and root.  Done results revealed significant differences in all treatment. Thus, obtaining plants with a higher quantity and quality of food that meets the consumer’s need and increases the marketing value of the varieties.